Comparative Evaluation of Two Doses of Midazolam Combination with Ketamine as General Anesthesia in rabbits - Khalaf, Falah H.; Hussein, Raad Mahmood; Al-Zuhairi, Ahmad Hanash (Diyala Journal for Veterinary Sciences, 2024)
Amis: The study’s objective evaluated the anesthesia produced by varying concentrations of mid-azolam and ketamine on hematological and clinical parameters. Methods: Twenty mature local breed rabbits, both sexes, were randomly categorized into two groups and with intramuscular injections of midazolam (1 mg/kg BW) and ketamine (30 mg/kg BW) in the first group, and midazolam (3 mg/kg BW) and ketamine (30 mg/kg BW) in the sec-ond. They clinically evaluated for 120 minutes, 15-minute intervals starting at zero minutes be-fore to anesthesia. In addition to body temperature, heart rate, respiration rate, analgesia, and muscle relaxation, further variables were also taken into explanation, including the phases of an-esthesia (induction of anesthesia, surgical anesthesia, and recovery period). Results After anesthesia, the clinical respiratory parameters of both groups showed significant differences at the P0.05 level between the evaluation points in the second group and the zero time group. Furthermore, with a significant difference in both groups, a slight drop in rectal body tem-perature at 30, 45, and 60 minutes after anesthesia. In all groups, there were significant variations in heart rate between zero and 60 and 75 minutes, but not between zero and five minutes. In the categories of RBCs, WBC, HB, and PCV, hematological tests indicated only modest variance with no significant changes; only WBCs after a minute shown a mildly substantial rise concern-ing control levels. Conclusion: In the present study, midazolam and ketamine were combined to provide a clinically effective general anesthetic. Both groups recovered quickly and easily, however it seemed that the second group have more time to recover from the anesthesia than the first group required. During induction, there was no apnea or nervousness.